Blocking MCT4 SUMOylation inhibits the growth of breast cancer cells. Issue 10 (4th August 2021) - Hu, Xiao; Liu, Zhanzhao; Duan, Xianxian; Han, Xiao; Yuan, Mengci; Liu, Lingyan; Xia, Xiaojun; Li, Ning; Qin, Junfang; Wang, Yue
Abstract: Monocarboxylate transporter 4 (MCT4) is highly expressed in various types of solid neoplasms including breast cancer (BC); however, the pro‐tumor functions underlying its increased expression have not been explained. Here, we examined the roles of posttranslational modifications to MCT4 in BC, particularly SUMOylation. Our findings revealed that SUMOylation of MCT4 inhibited its degradation and stabilized MCT4 protein levels, while ubiquitination facilitated MCT4 degradation. The E3 ubiquitin ligases β ‐TRCP and FBW7 interacted with MCT4 at the DSG‐box and TPETS sequences, respectively, and Lys448 (K448) of MCT4 could be modified by SUMO chains. Our key finding was that K448 was crucial for MCT4 SUMOylation. Moreover, mutations of K448 abolished MCT4 expression, delaying the growth of BC. This study suggested that SUMOylation of K448 increased MCT4 levels, and mutations of K448 in MCT4 could have therapeutic significance in BC.